A systematic review of margin status in retroperitoneal liposarcomas: Does the R0 margin matter? - Paik, Benjamin; Seo, Chin Jin; Tan, Joey Wee-Shan; Juan, Wen Kai Darryl; Soo, Khee Chee; Ong, Chin-Ann Johnny; Chia, Claramae Shulyn; Wong, Jolene Si Min (Frontiers in Oncology, 2022)
Retroperitoneal liposarcomas (RPLPS) are a rare tumor group for which current guidelines recommend aggressive en-bloc resection to attain microscopically negative (R0) margins. To ensure R0 margins, resection of adherent or adjacent organs is often required. However, it is still unclear if R0 margins confer any additional benefit to patients over a grossly negative but microscopically positive (R1) margin. We performed a systematic search of PubMed and Embase databases for studies including patients receiving R0 or R1 resection for RPLPS. 9 retrospective cohort studies, 1 prospective cohort study, and 49 case reports/case series were included. A total of 552 patients with RPLPS were evaluated: 346 underwent R0 resection and 206 underwent R1 resection. In the R0 group, 5-year overall survival (OS) ranged from 58.3 – 85.7%, local recurrence (LR) ranged from 45.5% – 52.3%. In the R1 group, 5-year OS ranged from 35% – 55.3%; LR ranged from 66.7– 91.7%. Amongst cohort studies, OS, disease-free survival (DFS), LR rate and local recurrence-free survival (LRFS) were significantly associated with R0 resections. Assessment of case series and reports suggested that R0 margin led to a slightly higher morbidity than R1. In conclusion, this review found R0 margin to be associated with reductions in LR rates and improved OS when compared with R1 margins, though accompanied by slight increases in morbidity. The roles of tumor histotype and peri-operative chemotherapy or radiotherapy was not well-elucidated from this review.